STUDI KOMPARASI KEPUTUSAN PEMBELIAN ANTARA AYAM GEPREK ABANG IRENG UMS DAN AYAM GEPREK KUMLOT UMS - Metdi Permadi; Siti Maryam; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to determine differences in purchasing decisions between Abang Ireng UMS geprek chicken and UMS Geprek Kumlot chicken in terms of Brand Image, Price and Variation of the menu. This method is called the comparative and quantitative methods with the aim of the comparative method with the aim of finding out the differences in purchasing decisions between variables. The sample of this study was 100 respondents consisting of 50 consumers of Abang Ireng Geprek chickens and 50 Kumlot geprek consumers. This study uses validity, reliability, to test the instrument using homogeneity analysis and independent sample t-test to test differences between variables. Data obtained from questionnaires for respondents. This study was tested using SPSS 20 software. The results of this study indicate that the Brand Image variable has no difference in purchasing decisions. Namely with the t value of the Brand Image variable of 0.753 with the criteria of t table> 0.05, this shows that there is no significant difference, while for the price variables and menu variations there is each difference to the purchase decision, namely the value of t count in the variable price of 0.018 with the criteria of t table